1987
DOI: 10.1002/jbm.820210107
|View full text |Cite
|
Sign up to set email alerts
|

Composites for use in posterior teeth: Composition and conversion

Abstract: The purpose of this investigation was to determine the composition, as well as the conversion after polymerization, of some dental composite materials. Eight posterior composites and two anterior composites were investigated. The weight and volume fractions of inorganic fillers were determined by combustion and pycnometric analyses. The monomers were analyzed qualitatively and quantitatively by high performance liquid chromatography, nuclear magnetic resonance spectroscopy, and gel permeation chromatography. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
57
3
16

Year Published

1991
1991
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(81 citation statements)
references
References 16 publications
3
57
3
16
Order By: Relevance
“…From the data available, it is clear that they are either based on BisGMA/TEGDMA comonomers (CD, CN, CP) or on the same comonomers plus UEDMA for partial substitution of BisGMA (MC, LX), as the latter has been shown to improve C=C conversion. [9][10] In all the DCB products tested, LC provided better results than 10 minutes of SC, which confirms the documented advantages of light curing, at least during the initial setting stages. 4 An interesting finding was that the control LC material (CP) demonstrated a significantly lower amount of %RDB than the corresponding dual-cured material (CD) when tested in the LC mode, despite both containing the same monomers and CD incorporating a slow setting SC mechanism.…”
Section: Discussionsupporting
confidence: 67%
“…From the data available, it is clear that they are either based on BisGMA/TEGDMA comonomers (CD, CN, CP) or on the same comonomers plus UEDMA for partial substitution of BisGMA (MC, LX), as the latter has been shown to improve C=C conversion. [9][10] In all the DCB products tested, LC provided better results than 10 minutes of SC, which confirms the documented advantages of light curing, at least during the initial setting stages. 4 An interesting finding was that the control LC material (CP) demonstrated a significantly lower amount of %RDB than the corresponding dual-cured material (CD) when tested in the LC mode, despite both containing the same monomers and CD incorporating a slow setting SC mechanism.…”
Section: Discussionsupporting
confidence: 67%
“…In Tetric Ceram, the weight percent of diluent monomer, TEGDMA, is about 20% of the total monomer. This is a lower value compared to the 30-50% of diluent content reported by Ruyter and Øysaed [11]. High filler loading in Z100 and a lower percentage of diluent monomer in Tetric Ceram may be the reason for the low polymerization shrinkage observed.…”
Section: Discussioncontrasting
confidence: 51%
“…18 From another viewpoint, it is also possible that nanometric fillers promote a light scattering effect (similar to minifilled particles) that would not permit light energy to activate the deepest resin composite layers. 19 A recent study of the polymerization depth of dental composites observed lower microhardness values at a polymerization depth of more than three millimeters. 20 This was explained by the light scattering effect that decreases the degree of conversion of the material.…”
mentioning
confidence: 99%